2019
DOI: 10.1007/s11033-019-05091-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, in vitro and in planta expression of a necrosis-inducing Phytophthora protein 1 gene npp1 from Phytophthora cinnamomi

Abstract: The soil-borne oomycete Phytophthora cinnamomi is a highly destructive Phytophthora species associated with the decline of forest. This pathogen secretes a novel class of necrosis-inducing proteins known as Nep1-like proteins (NLPs). In this work, we report the sequencing and molecular characterization of one of these proteins, more specifically the necrosis-inducing Phytophthora protein 1 (NPP1). The ORF of the npp1 gene (EMBL database AM403130) has 768 bp encoding a putative peptide of 256 amino acids with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Plant defense responsive cutters are induced and secreted by Phytophthora to some extent; it can be said that pathogenesis relies on protein-targeting motifs ( Bengyella et al, 2019 ). A necrosis-inducing protein isolated from P. cinnamon facilitates the colonization of host tissues during the necrotrophic stage by stimulating plant cell death by facilitating nutrient uptake by pathogens ( Martins et al, 2019 ). Effects of fungal and oomycete proteins have been shown to play an important role in apoplasts for adaptation, with recent advances in understanding the role of these proteins in escaping chitin-induced immunity ( Rocafort et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant defense responsive cutters are induced and secreted by Phytophthora to some extent; it can be said that pathogenesis relies on protein-targeting motifs ( Bengyella et al, 2019 ). A necrosis-inducing protein isolated from P. cinnamon facilitates the colonization of host tissues during the necrotrophic stage by stimulating plant cell death by facilitating nutrient uptake by pathogens ( Martins et al, 2019 ). Effects of fungal and oomycete proteins have been shown to play an important role in apoplasts for adaptation, with recent advances in understanding the role of these proteins in escaping chitin-induced immunity ( Rocafort et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A P. cinnamomi NPP1 has been reported in a study where the authors investigated the expression of the gene using RT-qPCR, both in vitro, using different carbon sources, and in vivo, during infection of Castanea sativa roots [139]. A decrease in NPP1 expression was noted between 12 and 24 h post-inoculation (hpi) with a significant increase at 36 hpi, suggesting a complex host-pathogen interaction.…”
Section: Nep1-like Protein (Nlps)mentioning
confidence: 99%
“…Moreover, the same study revealed that β-cinnamomin is secreted at different life stages of P. cinnamomi, through the use of a β-cinnamomin immune-labeling [72]. Furthermore, recent studies using bioinformatics approaches, heterologous protein expression system and molecular biology techniques have characterized necrosis-inducing Phytophthora protein 1 (NPP1) elicitin and an endo-1,3-β-d-glucosidase of P. cinnamomi [73,74].…”
Section: How Biotechnology Can Be Useful To Understand P Cinnamomi Amentioning
confidence: 99%